2013
DOI: 10.1007/s00192-013-2164-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling manual perineal protection during vaginal delivery

Abstract: Objective The aim of this study was to evaluate whether a previously identified modification of Vien-nese method of perineal protection remains most effective for reduction of perineal tension in cases with substantially smaller or larger fetal heads. Methods A previously designed finite element model was used to compare perineal tension of different modifications of the Viennese method of perineal protection to "hands-off" technique for three different sizes of the fetal head. Quantity and extent of tension t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 31 publications
0
39
0
2
Order By: Relevance
“…Based on stereo‐photogrammetric analysis of perineal deformation during fetal head expulsion, MPP seems to produce its protective effect via dispersion of the highest perineal tension over a wider surface area. This is mainly achieved by a reduction in the transverse perineal tension using the accoucheur’s thumb and index finger alongside the vaginal opening . Subsequent computational biomechanical studies showed that such maneuver can produce up to a 30% reduction in relative tension in the perineal region, dependent on the precision of its execution .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on stereo‐photogrammetric analysis of perineal deformation during fetal head expulsion, MPP seems to produce its protective effect via dispersion of the highest perineal tension over a wider surface area. This is mainly achieved by a reduction in the transverse perineal tension using the accoucheur’s thumb and index finger alongside the vaginal opening . Subsequent computational biomechanical studies showed that such maneuver can produce up to a 30% reduction in relative tension in the perineal region, dependent on the precision of its execution .…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly achieved by a reduction in the transverse perineal tension using the accoucheur's thumb and index finger alongside the vaginal opening. [17][18][19] Subsequent computational biomechanical studies showed that such maneuver can produce up to a 30% reduction in relative tension in the perineal region, dependent on the precision of its execution. 18,20,21 Indeed, the maneuver is most effective when the thumb and index finger were applied 12 cm apart, 2 cm anterior to the posterior fourchette and approximated medially study took place in three maternity units that support manual perineal protection policy in three European countries (Czech Republic, Slovenia and the UK).…”
Section: Introductionmentioning
confidence: 99%
“…The second component is the application of fingers on the posterior perineum at crowning in a manner that dissipates or relieves pressure on its central part, where the stress is maximal, and which if it tears, would most likely result in a direct breach of the anal sphincters. There could be interindividual variations to this technique, and the true contribution of this technique to the prevention of OASI would be difficult to quantify, unless pressure measurements of actual perineal stretching or deformation are available [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The current UK based maternity practice at second stage of labour involves two techniques 9,10 : 1) 'hands-on', where one hand of the practitioner applies pressure on the fetal head while the other hand supports the perineum, 2) 'hands-poised', where the hands of the practitioner are poised, ready to apply light pressure on the fetal head to avoid rapid expulsion. Most often, however, this latter technique has been misinterpreted as a 'hands-off technique'.The Royal College of Midwives (RCM) in 2012, and in line with the NICE 2007 guidance on intrapartum care, has suggested that the available evidence is inconclusive as to whether the 'hands-on' technique reduces the incidence of severe perineal trauma , which have however received heavy criticism from later studies as to the validity of their results and the robustness of their study design and methodology 14,15 . In the United Kingdom the incidence of OASIS for primiparous women has been reported to have tripled from 1.8% to 5.9%, over a 12-year period 8 .…”
mentioning
confidence: 99%
“…The Royal College of Midwives (RCM) in 2012, and in line with the NICE 2007 guidance on intrapartum care, has suggested that the available evidence is inconclusive as to whether the 'hands-on' technique reduces the incidence of severe perineal trauma , which have however received heavy criticism from later studies as to the validity of their results and the robustness of their study design and methodology 14,15 . In the United Kingdom the incidence of OASIS for primiparous women has been reported to have tripled from 1.8% to 5.9%, over a 12-year period 8 .…”
mentioning
confidence: 99%